Critical Discourse Analysis Sara Mils in the Online News Text about the Sinking of Ships at Indonesian Waters - Syarifa Rafiqa (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract: This study examines how the women in this case Minister Susi are presented in the news text about the sinking of ships in Indonesian waters. Research was conducted on the 5 most popular online news sites in Indonesia. The analysis used is the critical discourse analysis of Sara's perspective, by analyzing 3 elements, namely the position of the subject-object, the position of the reader, and the position of the media. The results of this study indicate that, the position of the subject is the writer of the news and the object is Susi, because women in online news texts define their position and they can also present themselves and reinforced the author by displaying the ideas of the object. The position of the reader is the insertion of cultural codes, the reader will approve the ideas of the author on the orientation of values so that readers will place himself in the main character in the text. Media position on online news sites that provide positive images, namely detik.com, kompas.com and okezone.com. While those who reported neutrally were tribunnews.com and republika.co.id.